Track design and realization of braiding for three-dimensional variably shaped cross-section preforms. (March 2021) - Guowei, Shao; Zhihong, Sun; Qihong, Zhou; Zhenxi, Wang; Bing, Wang; chang, Xu; Tao, Fang; Hua, Lin
The preforms of three-dimensional (3D) braided composites have a monolithic structure that is braided with high-performance fibers using 3D braiding technology. Compared with traditional laminate composites, braided composites are widely favored because of their superior overall performance and mechanical properties. The capability of fabricating various yarn structures with a flexible 3D rotary braiding method, however, has not been systematically investigated, especially for a variable-section braiding structure. In accordance with the principles of braiding technology and the characteristics of a 3D braiding structure, in this study, we examined a braiding technology for the production of 3D variably shaped cross-section fabric, focusing on three key factors: the topology design of tracks, the arrangement of carriers, and the matrix algorithm of the braiding of variably shaped cross sections. We calculated new kind of structural synthesis approach to a 3D braiding track for a variable section based on the carrier arrangement characteristic method and completed the entire braiding scheme of the variable cross section. In addition, this approach represents an important step toward a simplified understanding of the carrier motion and the operator-independent operation of a 3D rotary braiding machine.